Environmentally Friendly Public Transport - Marian KOPCZEWSKI; Grzegorz WISNIEWSKI (Communications of International Proceedings, 2022)
The problems of the sustainable development of the transport system are currently very important and often analyzed. It is about promoting transport that is efficient, cost-effective and meets the expectations of society. At the same time, such transport should minimize its negative impact on public health, the environment, the economy and urban planning.
Keywords: Transport; Ecology; Sustainable Development